The development of competency model for primary school teachers implementing authentic learning approach - Vijaya Letchumy Baskaran (2022)
A competency model for primary school teachers implementing authentic learning approach was developed through this study. This study had identified and evaluated the effects of mediator variables and moderator variables on the study constructs. The research design is mixed method approach. In total there are five objectives to be achieved in this study. Constructs and research instruments were constructed based on a review of the literature on previous competency theories and models, the results of the analysis of focus group interviews and expert panel evaluation. The developed instrument was used for data collection from primary school teachers in Perak (n = 565) with a response rate of 52 %. Structural Equation Modelling (SEM) statistical testing through IBM SPSS Amos software was used to analyse the main statistics of this study to obtain parameter estimates and model testing which in turn will produce a proposed model that meets the specified fit index. The main findings of the study have successfully identified that Assessment Knowledge (ASK), Curriculum Knowledge (CUR), Classroom Management Skills (MAN), Communication Skills (COM) and Teacher Sensitivity (TES) are the main factors influencing the Professional Commitment (PRO) and Authentic Learning Competency (ALCoM) significantly. The overall SEM analysis had identified that the variables ASK, CUR, MAN, COM, and TES accounted for 66% of the variance for PRO and 73% of ALCoM. The study had also identified that PRO acted as mediator variable between ASK, CUR, MAN, COM, TES and ALCoM. Gender and Work Experience constructs were the moderating variables in this study. In conclusion, this study has been able to identify the components involved in developing the competency model implementing the Authentic Learning approach amongst the primary school teachers, which can support the process of instilling 21st Century Skills contextually in line with the requirements of the Malaysian education system. The development of the competency model can serve as a constructive guide to policy makers, MOE and other stakeholders to intensify the development of professional teaching competencies and further increase the level of knowledge, skills and values needed by primary school teachers to implement Authentic Learning approach based on ALCoM Model.